Епідемії та боротьба з ними в Україні (кінець ХVIII – початок ХХ ст.) - Шандра, В.; Карліна, О. (Український історичний журнал, 2020)
Мета статті полягає у висвітленні епідемічної ситуації в «українських ґуберніях» Російської імперії із кінця ХVIII до початку ХХ ст., розгляді заходів органів влади (включно з самоврядними інституціями) щодо подолання пошестей, у тому числі практичного використання наукових
напрацювань і санітарно-гігієнічних знань для недопущення спалахів захворюваності. Методологія дослідження ґрунтується на загальних принципах науковості та історизму з використанням
проблемно-хронологічного, порівняльно-історичного, просопографічного, статистичного методів.
Наукова новизна. На підставі аналізу історичних джерел і наукової літератури з’ясовано види,
часові межі й локалізацію епідемій, а також їх соціально-демографічні наслідки. Відзначено, що в
боротьбі з пошестями тривалий час держава віддавала перевагу карантинним методам і значно
менше уваги звертала на розвиток мікробіології та епідеміології. Досягнення медицини повільно
входили у протиепідемічну практику. Недотримання широким загалом санітарно-гігієнічних норм
ускладнювало боротьбу з недугами. Висновки. Інфекційні хвороби потрапляли в Україну переважно зі східного напрямку. Їх поширенню сприяли зростання чисельності міських жителів, переміщення військових континґентів, забруднення води побутовими і промисловими відходами, відсутність майже до кінця ХІХ ст. навичок соціальної й особистої гігієни. Окрім карантину, боротьба
з епідеміями включала створення заразних бараків, де хворих ізолювали та лікували, залучення
додаткового медичного персоналу, дезінфекцію територій і житла, розгортання санітарних постів,
забезпечення населення дезінфікуючими засобами. Гостро давалася взнаки проблема ефективної організації управління та контролю за діями карантинних і медичних служб у масштабах
як окремих територій, так і всієї держави. Державна політика в галузі медичного забезпечення
населення не стимулювала активність органів самоврядування. Проте незважаючи на урізання
повноважень і фінансових ресурсів, земства та міські управи загалом змогли організувати дієву
допомогу в подоланні пошестей. Їхні зусилля активно підтримувала інтеліґенція, пропаґуючи в
популярній літературі правила гігієни й санітарні норми. The purpose of the article: to cover the spread of epidemics in the Ukrainian provinces
from the end of 18 to the beginning of 20 century and to consider the measures of the authorities
(including self-governing institutions) to overcome them, as well as to show the practical use of
scientific achievements and sanitary and hygienic knowledge to prevent epidemics. The research
methodology is based on the general principles of scientificity and historicism using problemchronological,
comparative-historical, prosopographic and statistical methods. Scientific novelty.
Based on the analysis of historical sources and scientific literature, there were clarified the types, time
limits and localization of epidemics, as well as their social and demographic consequences. It was
noted that for a long time in the fight against epidemics the state preferred quarantine methods and
paid much less attention to the development of microbiology and epidemiology. Doctors-researchers,
without sufficient government support, resorted to self-infection to monitor the disease clinic. Medical
scientific knowledge was slowly becoming a part of the practice of preventing epidemics. Zemstwo and
city medical institutions did not receive adequate legislative support for their activities. Their work was
not coordinated, in particular, in providing patients with medicines, carrying out preventive work among
the population etc. Failure of the general population of peasants and burghers to comply with sanitary
and hygienic norms complicated the fight against epidemics. Conclusions. Infectious diseases that led
to mass disease came to Ukraine mainly from the East. Their spread was facilitated by the following
factors: an increase in the number of urban residents, the movement of significant military formations
in the western direction, water pollution by household and industrial waste, the absence of almost
until the end of the XIX century. Social and personal hygiene skills. In addition to quarantine, the
fight against epidemics included the deployment of temporary infectious barracks, the involvement of
additional medical personnel, the isolation and treatment of patients, the disinfection of infected areas
and housing, the establishment of sanitary posts on transport, the provision of disinfectants etc. In
the fight against epidemics, the state faced the problem of effective organization of management and
control over the actions of quarantine and medical services in both individual provinces and the state
as a whole. There was no single central government coordinating body with special competences to
prevent epidemics, which complicated the work in this area. Doctors, researchers and practitioners,
medicalized epidemics, pointed to their dependence on social and economic factors. The prevailing
opinion was that infectious diseases are caused by pathogens that provoke the disease in favorable
conditions. Discussions about the ways of infection (physical contact, the presence of miasms in the
air, microbial theory) influenced the use of methods to prevent epidemics. State policy in the field of
medical care did not stimulate the activity of self-government bodies. However, despite the reduction
of powers and financial resources, zemstvos and city councils in general were able to organize effective
assistance to cities and villages in overcoming mass diseases. They were actively supported by the
intelligentsia, promoting hygiene rules, sanitary norms and preventive work by distributing books of
popular content.